Using risk mitigation approaches to define the requirements for software escrow - Rode, Karl (Rhodes University, Faculty of Science, Department of Computer Science, 2015)
Two or more parties entering into a contract for service or goods may make use of an escrow of the funds for payment to enable trust in the contract. In such an event the documents or financial instruments, the object(s) in escrow, are held in trust by a trusted third party (escrow provider) until the specified conditions are fulfilled. In the scenario of software escrow, the object of escrow is typically the source code, and the specified release conditions usually address potential scenarios wherein the software provider becomes unable to continue providing services (such as due to bankruptcy or a change in services provided, etc.) The subject of software escrow is not well documented in the academic body of work, with the largest information sources, active commentary and supporting papers provided by commercial software escrow providers, both in South Africa and abroad. This work maps the software escrow topic onto the King III compliance framework in South Africa. This is of value since any users of bespoke developed applications may require extended professional assistance to align with the King III guidelines. The supporting risk assessment model developed in this work will serve as a tool to evaluate and motivate for software escrow agreements. It will also provide an overview of the various escrow agreement types and will transfer the focus to the value proposition that they each hold. Initial research has indicated that current awareness of software escrow in industry is still very low. This was evidenced by the significant number of approached specialists that declined to participate in the survey due to their own admitted inexperience in applying the discipline of software escrow within their companies. Moreover, the participants that contributed to the research indicated that they only required software escrow for medium to highly critical applications. This proved the value of assessing the various risk factors that bespoke software development introduces, as well as the risk mitigation options available, through tools such as escrow, to reduce the actual and residual risk to a manageable level.
Keywords: Escrows; Source code (Computer Science)